The Role of Social Accelerators in Promoting Authentic Leadership in Social Entrepreneurs - Ignacio Alvarez de Mon; Margarita Núñez-Canal; María de las Mercedes de Obesso (Business Ethics and Leadership)
This paper analyzes the role of social accelerators in fostering authentic leadership profiles among social entrepreneurs who are managing high-impact social enterprises associated with such accelerators. The research adopts a qualitative and descriptive approach, focusing on narratives from selected social entrepreneurs supported by a Spanish social accelerator. Nine social entrepreneurs were interviewed, embedded in an ecosystem organized and managed by the accelerator. These social entrepreneurs have been highly successful in terms of having a positive impact on their communities, with the ability to obtain outside funding for their operations based on their performance. The case study method provided a profound analysis of the chosen cases. The study builds on existing literature linking social entrepreneurship and Authentic Leadership, adapting the theoretical framework to the context of Spanish social entrepreneurs. Through the analysis of social entrepreneurs' narratives and perceptions, the research highlights the mutual influence between social accelerators and social entrepreneurship, emphasizing the involvement of corporations and their top managers. The findings confirm that the interaction between social entrepreneurs and the accelerator supports the evolution of these entrepreneurs as authentic leaders, ultimately enhancing the impact and success of their ventures. The Authentic Leadership profile of these entrepreneurs develops while leading their social impact projects with the help of a social accelerator. This profile is based on the presence of some key characteristics: triggering events in the form of critical life experiences, a deep reflection on fundamental personal values, self-aware personalities in the process of developing their projects, efficiency and effectiveness compatible with accomplishing a social purpose, and a rich social network built around long-term relationships with valuable stakeholders. These results offer valuable insights for further applications in leadership development within the social enterprise sector.